Phenolic Extract of Seagrass, Halophila ovalis Activates Intrinsic Pathway of Apoptosis in Human Breast Cancer (MCF-7) Cells. (7th February 2021) - Sharma, Harshita; Stephen, Nimish Mol; Gopal, Sowmya Shree; Udayawara Rudresh, Deepika; Kavalappa, Yogendra Prasad; Haranahalli Shivarudrappa, Arpitha; Gavirangappa, Hithamani; Ponesakki, Ganesan
Abstract: The marine ecosystem is considered as a treasure of numerous novel biologically active molecules. We investigated the anticancer potential of the phenolic extract of Halophila ovalis in breast cancer (MCF-7) cells and characterized the possible underlying molecular mechanism. The phenolic extract (5 µl) of H. ovalis effectively inhibited the growth of MCF-7 cells. The results of DAPI staining indicated that this phenolic extract potently induces apoptosis in MCF-7 cells which was observed by increased chromatin condensation in the treated cells. An increased expression of the active fragments of an executioner caspase, caspase 3 in phenolic extract-treated MCF-7 cells further confirms this apoptosis induction. In consequence, the loss of mitochondrial membrane potential was noticed in treated cells. The protein expression analyzes show decreased expression of the anti-apoptotic protein, Bcl-2, and DNA repair enzyme, PARP in treated cells indicating the probable molecular targets of apoptosis. Further, the phenolic extract of H. ovalis blocked the antioxidant defense system in MCF-7 cells by down-regulating the protein expression of a major transcription factor, Nrf-2 and regulatory antioxidant enzymes, SOD-2 and HO-1. These results show the presence of chemopreventive compound(s) in the phenolic extract, which offers a platform for future studies to identify the active principles.